Breaking Up the "Religious" Conflict: Some Comparative Perspectives - Fannani, Bakhruddin (ULUL ALBAB Jurnal Studi Islam, 2004)
Actually, we can take advantage of it - or even stop inter-religious "conjunctions", because all religions have very strong relationships with the community. That is, every religion - doctrine, dogma, teaching, and practice - have the same opportunity to influence the community. However, this needs to be taken more seriously by all parties.